Interacting boson modeling in the nuclear structure of deformed uranium isotopes - Дәлелханқызы, Анар (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2025)
One of the most pressing and complex issues in nuclear physics is the absence of a universal and comprehensive theory that fully describes the interaction processes between nucleons. These interactions exhibit a high degree of complexity and require consideration of the internal structural parameters of nuclear systems, including potential fields and the averaged motion laws of nucleons. Nuclear states at low energy levels are typically analyzed within the framework of specific model concepts. In such models, nucleons are assumed to move within an average potential field, and their mutual interactions are generally limited to two-body forces. A comparable analogy can be drawn with the motion of electrons within an atom, although the nature of nuclear forces is fundamentally different — they are significantly stronger and operate at very short distances. A particularly significant aspect of nuclear structure research is the study of collective motions, i.e., coordinated oscillations or rotations involving groups of nucleons. These movements directly affect key spectral parameters that define the internal structure of the nucleus. From a theoretical perspective, these phenomena were first extensively studied by O. Bohr and B. Mottelson. Within the framework of models describing the geometric shape of the nucleus, they provided a detailed interpretation of the physical nature of collective motion and linked it to deformation characteristics. Specifically, it was demonstrated that low-energy excitations are closely associated with the quadrupole deformation parameter. In this scientific study, we employ a theoretical approach based on the interacting boson model (IBM) incorporating SU(5) symmetry. Our aim is to provide a quantitative description of the structure of three different isotopes of the spheroidal Ruthenium element. In this context, we calculate the B(E2) transition probability parameter, which characterizes nuclear energy levels and electromagnetic radiation probabilities, and compare the theoretical results with existing experimental data. The outcomes of this research contribute to assessing the accuracy of nuclear models and improving the effectiveness of nuclear structure characterization.